Cycling as Transportation & COVID-19: Advantages of Shared Bicycles during Epidemics - Vahid Saatchian; Amin Azimkhani; Mutlu Türkmen; Dorri Dolatkhah Laein (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
In addition to the environmental problems that have plagued human life in recent decades, the outbreak of the coronavirus epidemic has endangered people's health and adversely affected their lives in other ways. Therefore, the present study aimed to investigate the advantage of using shared bicycles (SB) during the outbreak of epidemics. For this purpose, 310 male subscribers of an SB system were examined. The research tool was a questionnaire taken from studies. The results showed that the environmental and health advantages were favourable, but the place advantage indicated a relatively unfavourable situation. The results of the structural equation model also showed that the advantages of using an SB based on the highest impact are the motivational advantage, health advantage, environmental advantage, social advantage, financial advantage and place advantage. These results can provide useful solutions for governments to reduce environmental risks and maintain health and physical activity during epidemics.